2016
DOI: 10.1016/j.janxdis.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Intolerance of uncertainty in emotional disorders: What uncertainties remain?

Abstract: The current paper presents a future research agenda for intolerance of uncertainty (IU), which is a transdiagnostic risk and maintaining factor for emotional disorders. In light of the accumulating interest and promising research on IU, it is timely to emphasize the theoretical and therapeutic significance of IU, as well as to highlight what remains unknown about IU across areas such as development, assessment, behavior, and relationships to emotional disorders. The present paper was designed to provide a synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
198
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 237 publications
(221 citation statements)
references
References 134 publications
19
198
0
4
Order By: Relevance
“…More recent research has suggested that measures of IU should be designed around the specific situations in which they occur [1, 2, 44]. For example the items in the IUS-12 could be altered in future studies to make them specific to the diagnosis and treatment of lower back pain to improve our capacity to understand the role of IU in low back pain care.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…More recent research has suggested that measures of IU should be designed around the specific situations in which they occur [1, 2, 44]. For example the items in the IUS-12 could be altered in future studies to make them specific to the diagnosis and treatment of lower back pain to improve our capacity to understand the role of IU in low back pain care.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, intolerance of uncertainty (IU) could be one such psychological factor. IU refers to a dispositional characteristic that reflects a set of negative beliefs about uncertainty and its implications and represents an underlying fear of the unknown [1, 2]. IU has also been described as an incapacity to endure the aversive response triggered by the absence of salient, key or sufficient information [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reactivity to U-threat may therefore be a vulnerability factor for problematic alcohol use that precedes AUD onset. In addition, because sensitivity to uncertainty is posited to be a dispositional characteristic that emerges early in life and has neurobiological underpinnings (Shihata et al, 2016; Shankman et al, 2014), exaggerated reactivity to U-threat may be an endophenotype for AUD.…”
Section: Introductionmentioning
confidence: 99%